Global Financial Stability Report, April 2006 : Market Developments and Issues - Chapter 2; The Influence of Credit Derivative And Structured Credit Markets on Financial Stability. (Global Financial Stability Report; Global Financial Stability Report ;, 2006)
This paper examines the influence of credit derivative and structured credit markets on financial stability. Credit derivative and structured credit markets have grown rapidly in size and complexity in recent years. This paper reviews the growth of the credit derivative, the factors that have influenced their growth, how they have increasingly facilitated risk transfer, and their implications for financial stability. The paper also presents a discussion of policy implications and recommendations concerning these relatively new markets and related challenges.